(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the compliance level of nurses in fall prevention practices for patients in hospitals in Ho Chi Minh City in 2024 and to identify related factors. Method: A descriptive cross-sectional study was conducted on 312 nurses at four district-level hospitals in Ho Chi Minh City from August to October 2024. Results: The study recorded an average age of 39.2 years among participating nurses, with the majority being female (77.6%). Most nurses held either a college degree (54.2%) or a university degree (44.9%), with an average of 15.8 years of clinical experience. Among them, 77.9% had previously attended a fall prevention training course. The study found that the overall compliance level in fall prevention practices was moderate, with an average score of 3.26 out of 5. Factors such as age, educational level, clinical experience, and especially participation in training courses were found to have a statistically significant positive impact on nurses’ compliance with fall prevention practices. Conclusion: It is necessary to strengthen continuous training and improve the professional capacity of nurses. Additionally, supervision of fall prevention practices in nursing care should be enhanced.